1989
DOI: 10.1128/iai.57.2.303-313.1989
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of adhesin and hemolysin virulence factors among uropathogenic Escherichia coli

Abstract: The pap, prs, pil, and hly operons of the pyelonephritic Escherichia coli isolate J96 code for the expression of P, F, and type 1 adhesins and the production of hemolysin, respectively; the afal operon of the pyelonephritic E. coli KS52 encodes an X adhesin. Using different segments of these operons as probes, colony hybridizations were performed on 97 E. coli urinary tract and 40 fecal clinical isolates to determine (i) the presence in the infecting bacteria of nucleotide sequences related to virulence operon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
3
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 33 publications
7
77
3
2
Order By: Relevance
“…The papG tWT gene was present only in one fecal strain. Prevalence of the papG seP gene (class II variant) and prsG tWT gene (class III variant) was not signi¢- cantly di¡erent between the cystitis and pyelonephritis strains, unlike other studies showing that the papG seP gene predominates in pyelonephritis strains while the prsG tWT gene is most frequent in cystitis strains [3]. However, the statistical analysis of our data showed that papG seP was associated with higher relative virulence than prsG tWT in the strains isolated from pyelonephritis.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The papG tWT gene was present only in one fecal strain. Prevalence of the papG seP gene (class II variant) and prsG tWT gene (class III variant) was not signi¢- cantly di¡erent between the cystitis and pyelonephritis strains, unlike other studies showing that the papG seP gene predominates in pyelonephritis strains while the prsG tWT gene is most frequent in cystitis strains [3]. However, the statistical analysis of our data showed that papG seP was associated with higher relative virulence than prsG tWT in the strains isolated from pyelonephritis.…”
Section: Discussioncontrasting
confidence: 87%
“…P ¢mbriae have three de¢ned PapG adhesin variants; class I variant encoded by the papG tWT gene, class II variant (P adhesin) encoded by the papG seP gene and class III variant (F adhesin) encoded by the prsG tWT gene [2]. It has been shown that P adhesin predominates in acute pyelonephritis strains, while F adhesin is most frequent in cystitis strains [3]. F1C ¢mbriae (encoded by the foc operon) are genetically related to S ¢mbriae and their nucleotide sequences share a high degree of homology [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Another constructed DNA probe, named drb (130), was a 260-bp PstI fragment of plasmid pIL14 (afa-1 operon) coding for the AfaE-I adhesin expressed by the uropathogenic Afa/Dr DAEC KS52 strain (243). This DNA probe has been used in epidemiological studies of the associ-ation of Afa/Dr DAEC with urinary tract infection (13,130,131,250,287,466,467). The results show a high positive correlation of the colony hybridization assay with the adhesion assay and the hemagglutination inhibition assay described above.…”
Section: Diagnosismentioning
confidence: 99%
“…afaBC/daaC positivity has been found in UPEC strains belonging to the B2 phylogroups (61). Epidemiological studies show that E. coli isolates expressing Afa/Dr adhesins are involved in cystitis in children (25 to 50%) and pyelonephritis in pregnant women (30%) (34,53,(55)(56)(57)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93). In addition, these pathogenic E. coli strains cause UTIs in pregnant women (30,90,91,(94)(95)(96)(97).…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%